Effect of feeding processed poultry litter with or without molasses on the growth of buffalo calves - Teli, A A; Bakshi, M P S; Langar, P N (The Indian Journal of Animal Sciences, 2012)
Saw dust (1-year-old) based layer poultry litter (PL) was deep- stacked (DS) or sun-dried (SD) and respective processed PL was mixed with 7% molasses, 1 % common salt as DSPL and SDPL supplements isonitrogenous to the conventional control concentrate mixture (C). The DSPL and SDPL supplements replaced 40% (w/w) C as experimental groups Tâ‚ and Tâ‚‚ , respectively. These concentrate mixtures were supplemented to wheat straw-based complete diets. Two growth trials of 90 days each were conducted on 15 Murrah buffalo calves (1Â½ - to 2-year-old and 139.5 Â± 5.5 kg live weight) divided equally into 3 groups were offered control (C), Tâ‚ and Tâ‚‚ complete diet as a single meal. In the first 90-day trial molasses was additionally mixed 0.2 kg/kg DM with Tâ‚ and Tâ‚‚ diets, whereas in the subsequent 90-day trial period molasses was not added. The comparable daily DM intake (DMI) under all the diets tested was associated with the highest digestibility of nutrients, available ME and N-retention only under the control diet. However, exclusion of molasses improved both the nutrient utilization and daily weight gain under the Tâ‚ and Tâ‚‚ diets. Similar trend was observed for the rumen parameters estimated in the study. The better performance of DSPL over SDPL complete diet showed the potential utility of deep-stacked PL in wheat straw-based complete diets for buffalo calves.